2006
DOI: 10.1073/pnas.0601874103
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid enhancement of memory requires arousal-induced noradrenergic activation in the basolateral amygdala

Abstract: Considerable evidence indicates that glucocorticoid hormones enhance the consolidation of long-term memories for emotionally arousing experiences but not that for less arousing or neutral information. However, previous studies have not determined the basis of such arousal-induced selectivity. Here we report the finding that endogenous noradrenergic activation of the basolateral complex of the amygdala (BLA) induced by emotional arousal is essential in enabling glucocorticoid memory enhancement. Corticosterone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

24
348
2
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 437 publications
(376 citation statements)
references
References 56 publications
24
348
2
2
Order By: Relevance
“…This PKA activity most likely reflects a general arousal effect rather than being a direct measure of task performance. In support of the view that glucocorticoids require arousal-associated noradrenergic activation in both increasing PKA activity and inducing cognitive effects (22), corticosterone administration to home cage control rats did not increase pPKA-s immunoreactivity levels in the mPFC (1.1% ± 3.5%; P = 0.77).…”
Section: Unilateral Glucocorticoid Administration Into the Mpfc Does Notmentioning
confidence: 59%
See 1 more Smart Citation
“…This PKA activity most likely reflects a general arousal effect rather than being a direct measure of task performance. In support of the view that glucocorticoids require arousal-associated noradrenergic activation in both increasing PKA activity and inducing cognitive effects (22), corticosterone administration to home cage control rats did not increase pPKA-s immunoreactivity levels in the mPFC (1.1% ± 3.5%; P = 0.77).…”
Section: Unilateral Glucocorticoid Administration Into the Mpfc Does Notmentioning
confidence: 59%
“…To determine whether working memory impairment and memory consolidation enhancement produced by bilateral glucocorticoid infusions are linked because of the recruitment of a common intracellular mechanism, we examined whether GR agonist effects on these two memory functions both depend on noradrenergic activity within the mPFC. We focused here on the noradrenergic system because prior evidence from our laboratory indicates that glucocorticoids crucially depend on training-induced noradrenergic activity within the BLA to enhance memory consolidation of emotionally arousing experiences (18,(21)(22)(23). Moreover, stress-induced activation of the noradrenergic system within the mPFC is known to induce working memory impairment (9), whereas a systemically administered β-adrenoceptor antagonist blocks corticosterone-induced working memory impairment (3).…”
Section: Unilateral Glucocorticoid Administration Into the Mpfc Does Notmentioning
confidence: 99%
“…Glucocorticoid hormones are known to enhance long-term consolidation of emotionally arousing events via often nongenomic interactions with norepinephrine and its intracellular signaling systems within the BLA (27,52). For example, it has been shown that a blockade of noradrenergic neurotransmission in the BLA with specific adrenoceptor antagonists prevents glucocorticoid effects on memory consolidation (53)(54)(55). Previous studies indicated that glucocorticoids may also interact with the endocannabinoid system.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, animal studies, show that the activation of the beta-2 receptors induce LTP in neurons in hippocampus (Hillman et al 2005a) and increase performance in tasks evaluating long-term memory and learning with the infusion of specific b2-agonists (Gibbs and Summers 2000), while b2-antagonists impaired memory consolidation (Gibbs and Summers 2005). More specifically, it has been shown that noradrenergic activation of the basolateral complex of the amygdala, involving b-adrenoreceptors, selectively enhances memory consolidation for emotionally arousing experiences (Roozendaal et al 2006). The consensus of these animal studies is that higher beta-2 adrenergic receptor activity enhances memory/learning.…”
Section: Discussionmentioning
confidence: 99%